Stakeholder salience and social responsibility: Study of small businesses in Malaysia - Nejati, Mehran; Amran, Azlan; Ahmad, Noor Hazlina (2015)
This study empirically examined the role of stakeholders’ influence on social responsibility practices of small businesses in Malaysia, and analysed the importance and current attention of small firms to these stakeholder groups using the Importance-Performance Matrix Analysis (IPMA). Findings of this study revealed that community’s influence and customers’ influence had significant positive impact on the social responsibility practices of small firms. Moreover, the results of IPMA for the social responsibility construct indicated that community’s influence had the highest importance for small businesses and was given the highest level of attention by the firms. In contrast, customer’s influence was given lower attention by small firms despite its high level of importance for social responsibility practices of the firm.